Transcranial direct current stimulation to modulate fMRI drug cue reactivity in methamphetamine users: A randomized clinical trial. Issue 17 (1st August 2022) - Ekhtiari, Hamed; Soleimani, Ghazaleh; Kuplicki, Rayus; Yeh, Hung‐Wen; Cha, Yoon‐Hee; Paulus, Martin
Abstract: Transcranial direct current stimulation (tDCS) has been studied as a therapeutic option to alter maladaptive brain functions associated with chronic substance use. We present a randomized, triple‐blind, sham‐controlled, clinical trial to determine the neural substrates of tDCS effects on drug craving. Sixty participants with methamphetamine use disorder were assigned to two groups: active tDCS (5 x 7 cm 2, 2 mA, 20 min, anode/cathode over the F4/Fp1) and sham stimulation. Neuroimaging data of a methamphetamine cue reactivity task were collected immediately before and after stimulation. There was a significant reduction in self‐reported craving after stimulation without any significant effect of time‐by‐group interaction. Our whole‐brain analysis demonstrated that there was a global decrease in brain reactivity to cues following sham but not active tDCS. There were significant time‐by‐group interactions in five main clusters in middle and inferior frontal gyri, anterior insula, inferior parietal lobule, and precuneus with higher activations after active stimulation. There was a significant effect of stimulation type in the relationship between electrical current at the individual level and changes in task‐modulated activation. Brain regions with the highest electric current in the prefrontal cortex showed a significant time‐by‐group interaction in task‐modulated connectivity in the frontoparietal network. In this trial, there was no significant effect of the one session of active‐F4/Fp1 tDCS on drug craving self‐report compared to sham stimulation. However, activation and connectivity differences induced by active compared to sham stimulation suggested some potential mechanisms of tDCS to modulate neural response to drug cues. Abstract : In this experimental RCT among methamphetamine users, the activation and connectivity differences induced by active transcranial electrical stimulation over prefrontal cortex compared to sham stimulation suggested some potential mechanisms of tDCS to modulate neural response to drug cues.